Fresh off the Boat and Off to the Presses: The Origins of Argentine Comics between the United States and Europe (1907–1945). Issue 2 (1st September 2019) - Gandolfo, Amadeo; Turnes, Pablo
Abstract : This article aims to analyse the origins and development of the comics industry in Argentina from a comparative and transnational perspective, positing its business model, professionalisation of artistic and editorial work and adoption of certain styles as part of a triangle in which Argentine comics are in constant dialogue with European (mainly Spanish, French and English) and US comics traditions. The article places a special emphasis on the latter. As part of the overall process of cultural modernisation, the early twentieth century encompasses a period in which the production of comics grew, was established and modified its creative patterns in all the countries involved in the study. Comics in Argentina consistently moved between innovation and imitation, with some original narrative and formal solutions that were sparked by a process of adaptation and mistranslation.